Safety and health management at construction sites : factors influencing unsafety behaviours on construction sites - Nurul Jannatul ‘Atiqah, Othman (2017)
In Malaysia, accident keep happen every day without a clear control. By utilizing the current safety practice at the construction sites, then identifying the unsafety behaviors among construction workers, the significant behavior of unsafety act can be detect. Accident control at construction sites is the largest issues the construction company had to face today. This work illustrates, a research study to find the factors influencing unsafety behaviors and accidents on construction sites in Kuantan, Pahang. The research was focused on contractors as the person who handles a project and their workers. In this work, all the previous study were investigated and was categorized based on methods of data collection, interviewed on construction sites, analytical methods and key findings. Additionally, from the data analyses, found that there are 5 main categories factors which are (1) site condition factors, (2) individual factors, (3) work group factors, (4) job factors and (5) management factors that have been identified. The respondents involve were 31 persons ranging from contractor Grade 7 that registered with the CIDB. The research present the utilized result of questionnaire survey conducted. The findings highlighted the importance of factors that may contribute to reducing the likelihood of unsafe behaviors and accidents through the promotion of site condition and individual features. The factors were rank under each group by the “Relative Important Index” method. The conclusions are made and further researches are necessary to provide better understanding about the risk of fatal towards the workers or the contractor. Recommendations are include to improving safety on construction sites based on better application of management and policy.